Poziom wykształcenia ludności województwa łódzkiego w II Rzeczypospolitej - Rzepkowski, Arkadiusz (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2015)
The censuses from 1921 and 1931 give information about the level of education in the Łódź province. The census from 1921 gives the data about the education profile of the population, the second one from 1931 about the ability of reading and writing within the population. At the beginning of the twenties, considering population at the age of ten and older ones, 40.05% of this community had the primary education. The illiterates made up a large group of 30.31%. 14.19% made up people who got their education at home. Only 3.79% of the inhabitants of the province had the secondary education. The index of the people who got higher education and vocational education was low. In 1931 in the group of the above mentioned population 73.14% possessed the skill of reading and writing, 21.42% did not possess these skills, 5.44% of the people could only read. The education of the Łódź province population was typical of the former Congress Kingdom of Poland terrains during the interwar period. The education was worse comparing to the education from the area of former German annexation yet better than the education of the population coming from Polish eastern frontier.